Monitoring of antibiotic resistance of Acinobacillus pleuropneumoniae isolated in the Russian Federation in 2012-2014 - A. V. Potekhin; V. S. Rusaleyev (Ветеринария сегодня)
Antibiotic resistance of 42 porcine Actinobacillus pleuropneumoniae isolates recovered from pigs in the Russian Federation in 2012-2014 has been monitored. Most of them proved to be sensitive to penicillins (85,7%), aminopenicillins (92,9%), III-IV-generation cephalosporins (100%), enrofloxacin (81,0%), erythromycin (85,7%) and florfenicol (95,2%). The majority of the isolates demonstrated resistance to tetracyclines, sulfanilamides and trimethoprim.